Synthesis of Ag-reduced graphene oxide nanocomposite by gamma radiation assisted method and its photocatalytic activity. (February 2016) - Hareesh, K.; Joshi, R.P.; Dahiwale, S.S.; Bhoraskar, V.N.; Dhole, S.D.
Abstract: Silver-reduced graphene oxide (Ag-rGO) nanocomposite was prepared in the presence of Isopropyl alcohol (IPA) and polyvinyl pyrrolidone (PVP) by gamma irradiation assisted method. UV–Visible spectroscopic results showed the peak of rGO and surface plasmon resonance of Ag nanoparticles. X-ray powder Diffraction (XRD) results revealed the formation of face centered cubic structured Ag nanoparticles along with rGO signature after irradiation. Transmission electron microscopy (TEM) results showed the decoration of Ag nanoparticles of size 10 nm on rGO sheet corroborating the UV–Visible spectroscopic and XRD results. Raman spectroscopic results of Ag-rGO showed the increase in the ratio of D to G band (ID /IG ) after gamma irradiation. The prepared Ag-rGO nanocomposite was tested for the degradation of methylene blue (MB) and results distinctly enhanced photocatalytic degradation compared to bare Ag nanoparticles and graphene oxide. The prepared Ag-rGO nanocomposites act as photo-catalysts that utilize visible light as an energy source. Highlights: Ag-rGO nanocomposite has been prepared by gamma radiation assisted method. XRD results showed the formation of FCC structured AgNPs and reduction of GO. TEM results revealed the decoration of AgNPs on rGO. Ag-rGO sample showed good photocatalytic activity of MB compared to bare Ag and GO.